2007
DOI: 10.2355/isijinternational.47.1666
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties and Recrystallization Texture Evolutions of Phosphorus-bearing Non-oriented Electrical Steel Sheets

Abstract: The effect of phosphorus (P) on magnetic properties and also on recrystallization texture of non-oriented electrical steel sheets has been investigated to develop core materials with low core loss and high permeability. Specimens containing different amounts of P were cold-rolled to various thicknesses, i.e. with various cold-rolling reductions, and annealed for recrystallization and grain growth. Magnetic induction of the steel with a large amount of P was higher than that of the steel with a small amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…31) There are also some ribbon-like grains in decarburized bands with Ag contents of 0.003 wt% and 0.005 wt%. Tanaka et al 32) reported that impurity atoms segregate at grain boundaries could result in that the coincidence site lattice (CSL) boundaries have lower grain boundary energies and higher migration mobility than general grain boundaries. Thus, during decarburizing, the abnormal growth of ribbon-like grains in decarburized bands with Ag contents of 0.003 wt% and 0.005 wt% is likely to be a combination of grains having CSL boundaries with adjacent grains.…”
Section: Resultsmentioning
confidence: 99%
“…31) There are also some ribbon-like grains in decarburized bands with Ag contents of 0.003 wt% and 0.005 wt%. Tanaka et al 32) reported that impurity atoms segregate at grain boundaries could result in that the coincidence site lattice (CSL) boundaries have lower grain boundary energies and higher migration mobility than general grain boundaries. Thus, during decarburizing, the abnormal growth of ribbon-like grains in decarburized bands with Ag contents of 0.003 wt% and 0.005 wt% is likely to be a combination of grains having CSL boundaries with adjacent grains.…”
Section: Resultsmentioning
confidence: 99%
“…Tanaka et al [12] reported that the coincidence site lattice (CSL) boundaries have usually lower grain boundary energies and higher migration mobility than general grain boundaries in non-oriented electrical steels, especially when impurity atoms segregate at grain boundaries. Gomes et al [13] reported that the surface grains with ‹100›// ND orientation tend to rotate 15°along the Euler angle Φ to match {115} fiber which exhibits a Σ3 CSL relationship with both {110} and {111} fibers.…”
Section: Normalizing Annealed Bandsmentioning
confidence: 99%
“…The effect of the addition of segregation atoms other than Sn, for example, Sb [6][7][8][9] and P, [10][11][12][13][14] on the recrystallization texture has also been discussed. Tanaka et al 14) suggested that Σ9 coincidence site lattice (CSL) boundaries had priority in grain boundary migration under the solute drag effect of P, and this effect resulted in selective grain growth of the {φ 1 , Φ, φ 2 } = {25°, 10-15°, 45°} component; φ 1 , Φ, φ 2 are Bunge Euler angles representing crystal orientation. However, the behavior of grain boundary migration during grain growth under the existence of segregation atoms is still unclear.…”
Section: Effect Of Sn Addition On Evolution Of Primary Recrystallizatmentioning
confidence: 99%